2000
DOI: 10.1006/viro.2000.0238
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Hypervariable Region 1-Specific and -Cross-Reactive CD4+ T Cells in HCV-Infected Individuals Responsive to IFN-α Treatment

Abstract: The hypervariable region 1 (HVR1) of the putative envelope 2 protein of the hepatitis C virus (HCV) is the most variable part of the whole HCV polyprotein. Anti-HVR1 antibodies have been shown to protect against HCV infection, indicating that this region contains an important neutralization determinant. Recently we and others have demonstrated that HVR1 is also a T cell determinant able to activate helper T cell responses during HCV infection. In order to investigate the role of the immune response against HVR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…These authors postulated that this might be a mechanism for viral escape and persistence. Recent publications have shown that active cellular immune responses against the E2 are frequently present in persons infected with HCV (8,38). A similar observation can be inferred from a study of cell-mediated immunity during acute infection of chimpanzees, in which several CTL epitopes were identified in the E2 but not in the core region and the strength of CTL responses against these epitopes was associated with viral clearance (7).…”
Section: Discussionsupporting
confidence: 54%
“…These authors postulated that this might be a mechanism for viral escape and persistence. Recent publications have shown that active cellular immune responses against the E2 are frequently present in persons infected with HCV (8,38). A similar observation can be inferred from a study of cell-mediated immunity during acute infection of chimpanzees, in which several CTL epitopes were identified in the E2 but not in the core region and the strength of CTL responses against these epitopes was associated with viral clearance (7).…”
Section: Discussionsupporting
confidence: 54%
“…However, cellular immune responses may also play a role in the selection of viral variants [Eckels et al, 2000]. Indeed, it is now known that viral clearance is associated with persistently strong and broad T-cell responses [Del Porto et al, 2000;Lechner et al, 2000]. Rapid and serial changes in HVR-1 have been demonstrated in the acute phase of HCV infection as well [Sakamoto et al, 1994].…”
Section: Discussionmentioning
confidence: 98%
“…There is some evidence from other experimental systems that the same peptides are recognized by both Ig molecules and the TCRs of CD4 ϩ T cells (46,47). Two recent studies of human hepatitis C virus have mapped both Ig binding and T h epitopes to the hypervariable region of the env protein (48,49). In support of this theory, antibodies and CD4 ϩ T cells have been shown to recognize epitopes on the HIV env V2, V3, and V4 loops.…”
Section: Discussionmentioning
confidence: 99%